2012
DOI: 10.1007/s11250-011-0063-3
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of two serological tests for contagious bovine pleuropneumonia (CBPP) detection in an enzootic area using a Bayesian framework

Abstract: A Bayesian approach, allowing for conditional dependence between two tests was used to estimate without gold standard the sensitivities of complement fixation test (CFT) and competitive enzyme-linked immunosorbent assay test (cELISA) and the serological prevalence of CBPP in a cattle population of the Central Delta of the Niger River in Mali, where CBPP is enzootic and the true prevalence and animals serological state were unknown. A significant difference (P = 0.99) was observed between the sensitivities of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…These data are incomplete and does not address the prevalence of the disease, its distribution per region, and per age groups taking into account the herd structure. As for serological prevalence, an earlier report by Sidibé et al (2012), using the same serological test as in the present study, showed an overall individual prevalence of 14.1 % in the two regions of the Central Delta of the Niger River (Mopti and Segou). This first nationwide serological survey was therefore carried out for a better assessment of the prevalence of the disease and its distribution in Mali.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…These data are incomplete and does not address the prevalence of the disease, its distribution per region, and per age groups taking into account the herd structure. As for serological prevalence, an earlier report by Sidibé et al (2012), using the same serological test as in the present study, showed an overall individual prevalence of 14.1 % in the two regions of the Central Delta of the Niger River (Mopti and Segou). This first nationwide serological survey was therefore carried out for a better assessment of the prevalence of the disease and its distribution in Mali.…”
Section: Discussionsupporting
confidence: 76%
“…A parallel use of the c-ELISA test and the CFT is however advised for the serological diagnosis of CBPP as none of both tests can detect alone all positive animals during natural infection (Muuka et al 2011). This is confirmed in a study conducted by Sidibé et al (2012) by the observation of a negative conditional dependence involving a synergistic action of the parallel use of the two tests. This implies that to achieve maximum sensitivity, the two tests should be applied in parallel.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…It has some disadvantages, notably the difficulty of standardizing the production of the antigen or the presence of a certain number of non-specific positive reactions ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…CBPP screening and diagnosis depends on either conventional isolation of the etiological agent or serological and molecular tests. The complement fixation test (CFT) and a competitive enzyme-linked immunosorbent assay (cELISA) are the two primary serological tests recommended by the world organization for animal health (OIE) [ 11 ] and are both characterized by wanting test sensitivity and specificity [ 12 ].…”
Section: Introductionmentioning
confidence: 99%